2019
DOI: 10.1108/imds-08-2018-0370
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of narratives in civic crowdfunding: linguistic style and message substance

Abstract: Purpose The purpose of this paper is to explore how linguistic style and message substance influence persuasion in civic crowdfunding marketplaces in which written narrative pitch become a vital communication to attract private contributions to public goods and services. Drawing on the elaboration likelihood model (ELM), the authors operationalize the linguistic style of the narrative pitch as language power and message substance as issue-relevant argument quality. In this paper, the authors examine how charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 67 publications
0
55
0
Order By: Relevance
“…These results do not concur with the studies of Pitschner and Pitschner-Finn (2014) and Allison et al (2015), who found that non-profit projects have a higher probability of success and receive higher average contributions compared to for-profit projects. It should also be noted that this study considers the nature of the project a critical condition, since previous academic research on civic crowdfunding had not given much to this (Lee et al, 2019;Brent & Lorah 2019), focusing on the study of other drivers that can influence campaign success (among others, Brent & Lorah, 2019;Doan & Toledano, 2018;Hassna et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results do not concur with the studies of Pitschner and Pitschner-Finn (2014) and Allison et al (2015), who found that non-profit projects have a higher probability of success and receive higher average contributions compared to for-profit projects. It should also be noted that this study considers the nature of the project a critical condition, since previous academic research on civic crowdfunding had not given much to this (Lee et al, 2019;Brent & Lorah 2019), focusing on the study of other drivers that can influence campaign success (among others, Brent & Lorah, 2019;Doan & Toledano, 2018;Hassna et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The projects collecting funds through civic fundraising must result in an improvement in the lives of the community members and represent a 'shift to a more participatory form of urban planning' (Brent & Lorah, 2019, p. 122). The projects can have a profit or a not-forprofit nature, since civic crowdfunding is used also by social entrepreneurs to fund their social enterprises (Calic & Schevchenko, 2020;Lee et al, 2019). Social entrepreneurs often have limited access to traditional capital providers and this problem seems to sharpen 'when social ventures need capital to invest in commercial activities that generate earned income' (Calic & Mosakowski, 2016, p. 739).…”
Section: Nature Of Civic Crowdfunding Projectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Civic crowdfunding campaigns can also be found on reward-based crowdfunding CFPs, with both tangible and non-tangible rewards, such as the campaign to bail out the Greek people during the debt crisis (Indiegogo 2015). Table 19.1 Overview and typology of civic crowdfunding platforms (selection) Donation-and rewardbased CFPs narrative for the self-framing of civCF campaigns, which in turn informs their choice of a platform (Lee et al 2019). There is anecdotal evidence that all-purpose CFPs dedicated to creative industries introduced civCF campaigns categories because of repeated requests to host civCF campaigns, sometimes by project initiators which used the CFP for projects such as funding games, movies, and music albums, and then aiming to use their existing community on the platform to initiate projects with a civic purpose.…”
Section: Development Of Civic Crowdfundingmentioning
confidence: 99%